2016
DOI: 10.4102/jtscm.v10i1.211
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain integration in the South African conveyancing environment

Abstract: Background: Although conveyancing is a legal term, business management and specifically operations management principles also apply to the processes involved in conveyancing. From a business perspective, each organisation is usually concerned with its own profit margins and processes. In our global market, however, organisations now realise that they can no longer compete successfully on the basis of their internal operational efficiencies alone. They are therefore constantly aware of the need to improve not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…From a Sub Saharan Africa perspective, there is limited research into SCI with much research conducted from a South African perspective. For example, a recent study examined the SCI processes in a South African conveyancing industry and concluded that integrated information technology across SC partners optimizes process efficiency in the conveyancing SC (Amadi-Echendu and Krüger, 2016). Vermeulen et al (2016) studied SCI from the perspective of plastic manufacturers in South Africa's Gauteng province and found that customer price pressure and resource constraints motivated SCI efforts.…”
Section: Malawian Contextmentioning
confidence: 99%
“…From a Sub Saharan Africa perspective, there is limited research into SCI with much research conducted from a South African perspective. For example, a recent study examined the SCI processes in a South African conveyancing industry and concluded that integrated information technology across SC partners optimizes process efficiency in the conveyancing SC (Amadi-Echendu and Krüger, 2016). Vermeulen et al (2016) studied SCI from the perspective of plastic manufacturers in South Africa's Gauteng province and found that customer price pressure and resource constraints motivated SCI efforts.…”
Section: Malawian Contextmentioning
confidence: 99%
“…About 73.13% of the reviewed papers focused on collaborative relationships, 19.40% on cooperative relationships, 7.46% on transactional relationships, 2.99% on competitive and coopetitive relationships and 1.49% on coordination and adversarial relationships. x • [80] x • [81] x • [89] x • [82] x • [83] x • [84] x • [85] x • [78] x • [28] x • [87] x • [88] x • [90] x • [86] x • [91] x • [92] x • [93] x • [94] x • [96] x • [95] x • [97] x • [99] x • [98] x • [100] x • [18] x • [101] x • [19] x • [102] x • [27] x • [76] x • [103] x • [104] x • x • [107] x • [1] x • [74] x • [108] x • [109] x • [110] x • [26] x • [42] x • [112] x • [111] x • [113] x • [114] x • [115] x • [116] x • [45] x •…”
Section: B2b Supply Chain Relationshipmentioning
confidence: 99%
“…In the service industries, Yazici [95] evaluated buyer perceptions of the buyer-supplier collaborative relationship in the US service organisation. Other studies investigated the collaborative relationship between buyers and suppliers of facilities services [96], buyer and suppliers of facilities management services [97], different players in the South African conveyancing system [98] and collaborative activities between business service providers with other firms [99]. Pongsathornwiwat et al [100] investigated the hospitality managers' collaborative relationships with local suppliers and competitors.…”
Section: Trust-based Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, much attention is paid to the efficiency of the processes (Amadi-echendu and Kruger, 2015), due to the business environment that has become more competitive. Companies have had to reinvent themselves and work through networks, distributed elsewhere (Friedman, 2005).…”
Section: Business Process Management Systemsmentioning
confidence: 99%